Prospective data analysis of 1307 ventral hernia patients: Emergency hernia repair and smoking predict recurrence. (1st June 2022) - Soppe, S; Wirsching, A; Slieker, J; Keerl, A; Nocito, A
Abstract: Objective: Ventral hernias are frequent and hernia repair is regularly performed by general surgeons. Emergency repair is less frequent and can be challenging. Long-term outcomes comparing emergency and elective ventral hernia repair are scarce. Methods: Consecutive patients undergoing emergency and elective ventral hernia repair at our institution were prospectively entered in our HerniaMed database between August 2013 and February 2020. Ventral herniation included umbilical, epigastric and incisional hernias. Demographic-, perioperative- and outcome data were reviewed. Patients were contacted after one-, five- and ten years to assess long-term complications like hernia recurrence. Risk factors for emergency repair and hernia recurrence were assessed by univariate and multivariate analysis. Results: We included 1307 patients in our analysis. Emergency and elective hernia repair was performed in 11% and 89% of patients with one-year follow-op rates of 94% and 92%, respectively. Female gender, BMI >40 kg/m 2, ASA class 3 and 4, large size umbilical herniation (>4 cm) and epigastric herniation were more frequent in emergency compared to elective hernia repair. Furthermore, emergency repair led to increased length of hospital stay and increased overall complications (median 4 vs. 2 days, p<0.001 and 20% vs. 13%, p<0.021). Binary logistic regression analysis identified female gender (Odds ratio: 2.12 and 95% confidence interval: 1.13–3.99, p=0.019) and ASA class 3 and 4 (Odds ratio: 3.96 and 95% confidence interval: 1.96–7.99, p<0.001) to be independent predictors of emergency repair. After one year of follow up, hernia recurrence was found in 6% after emergency and in 2% of patients after elective repair (p=0.019). Emergency repair and smoking predicted hernia recurrence (Odds ratio: 4.48 and 95% confidence interval: 1.55–12.92, p=0.006; Odds ratio: 3.60 and 95% confidence interval: 1.39–9.32, p=0.008). Conclusion: Female gender and high ASA class were found to be independent predictors of emergency repair. Therefore, early elective ventral hernia repair should be considered for female and comorbid patients. In addition, since emergency repair and smoking were risk factors for recurrence, smokers should be counseled accordingly.